The Toxicity of Copper to Crocosphaera watsonii and Other Marine Phytoplankton: A Systematic Review - Lopez, Johann S.; Lee, Lillian; Mackey, Katherine R. M. (Frontiers in Marine Science, 2019)
The cupric ion (Cu2+) plays a dual role as both nutrient and toxicant to terrestrial and marine phytoplankton, functioning in multiple photochemical processes, as well as reactive oxygen species (ROS) production. This duality has been investigated through a variety of methods to determine the consequences of natural and anthropogenic copper introduction to algal ecosystem composition. Studies conducted over the past few decades have described the growth responses of many unique organisms to copper availability. Such observations are critical for describing the global distributions of major phytoplankton species in terms of global trace metal abundance; however, highly variable experimental practices impede direct inter-study comparison. The aim of this systematic review is to summarize the available data regarding the effects of copper concentration on diverse marine phytoplankton growth rates. Through extensive literary comparison, 143 studies were systematically reviewed, and data on copper concentrations and growth rates reported were extracted. From the data available, we conclude that trends in phytoplankton sensitivity to copper are mainly driven by a single study. We discuss the obstacles to inter-study comparison and detail both the concurring and conflicting results to date, with an emphasis on taxonomic trends and methodologies employed. Finally, we present the first copper sensitivity measurements for marine unicellular diazotrophs using three representative strains of the unicellular nitrogen-fixing cyanobacterium, Crocosphaera watsonii.